Bilingualism, raja rao and kanthapura - Ramanan, K.L. (University of Jaffna, 2012)
This paper has the objective of studying the novel Kanthapura in the light of bilingualism of the society in which Raja Rao, the author, lived and (re)presented it. Though the author was an individual, he was a representative of a society that is bilingual in nature. The society portrayed in the novel belongs to a village in Karnataka, India during the time of independence struggle. The language employed in the novel, is considered as a re-presentation of the society by an individual. Hamers and Blanc (1998) opine that the knowledge emerges from individuals’ experience and shared social experience. Therefore, all the possible utterances by an author are within the acceptable norms of the society. The novel Kanthapura was proposed to be analyzed as a text of the society. Descriptive analytical methodology was employed to analyze the bilingualism of the novel and based on it the bilinguality of the author was brought to the light. The text is analysed in this study as a product of the society where the individual representer of the text, i.e., Rao, was a part of it. Though Rao wrote in English, he was aware that he was a bilingual. His awareness of bilingualism made him select many linguistic features from several languages in India to present the society in the text. It is concluded that Rao’s awareness of bilingualism contributed much to the production of the text. It also helped him limit the application of particular language for certain domains. He employed his bilingual skills and resources to portray a society that is basically multilingual. Literal translation, code mixing, loan words and hybridization were utilized by the author to present the unique characteristics of the society in the text. The writer’s use of the social norms, beliefs and values add unique flavour to the text by rendering them through a local variety of English that has become the official language of India. As there is a similar linguistic trend in Sri Lanka, Rao could be considered the model for Sri Lankan bilingual writing.
Keywords: Bilingualism; Hybridization